The EMT activator ZEB1 accelerates endosomal trafficking to establish a polarity axis in lung adenocarcinoma cells - Priyam Banerjee (Nature Portfolio, 2021)
The way in which metastatic tumour cells control endocytic vesicular trafficking networks to establish a front-rear polarity axis that facilitates motility remains unclear. Here, the authors show that the EMT activator ZEB1 influences vesicular trafficking dynamics to execute cell polarity change.